Changes in soil nutrient status of a coarse-textured Ultisol and tomato growth performance following composted sawdust-household waste application - Benedict O. Unagwu; Chukwuma I. Obiora; Ginika M. Ajoagu (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Waste disposal poses serious environmental challenges to mankind. This precipitated the quest for an eco-friendly waste management approach to minimize the challenges wastes pose to the ecosystem and proffer alternative use for these wastes.Method A field study was carried out at the University of Nigeria Nsukka Teaching and Research Farm to investigate the effects of composted sawdust-household waste (SHW) with or without inorganic fertilizer addition on soil chemical properties and tomato performance. The experiment was arranged in a randomized complete block design with five treatments and three replications. The treatments were: 50% NPK + SHW 20 t/ha, SHW 40 t/ha, SHW 20 t/ha, 100% NPK, and Control.Result The amended treatments, except 100% NPK, increased the soil pH by 3-8%, available P by 14-29%, and soil organic matter by 1.5-9.8%. Control and 100% NPK treatments had no significant effect on the soil’s chemical properties. SHW 40 t/ha had significantly taller plants and a higher number of plant leaves relative to other treatments. The amended treatments recorded significantly weightier fresh root weight, dry root weight, fresh shoot weight, and dry shoot weight relative to the control treatment. Overall, SHW treatments application had more pronounced effects on plant biomass than on plant vegetative growth.Conclusion The study suggests that composted SHW can be a viable option over chemical fertilizer for tomato cultivation as well as good soil conditioners.